Research on General Scheme Technology of FXD3-J EMUs Car - Wei WANG; Shoujun YANG; Jingqi WANG (机车电传动)
The CR200J power concentrated EMUs are power concentrated EMUs, developed to enhance the comfort of China's railway general speed train passengers and the transportation capacity of passenger dedicated lines. The power car was designed based on the principles of interconnection, interoperability, and mutual control. After testing and assessment, it was finalized as FXD1-J and FXD3-J. Based on the positioning and function of the FXD3-j power car, this paper expounded the design principle, studied the design index of the top-level of the power car, and focused on the overall technical indicators such as the limit, axle weight, traction performance, equipment layout, and speed grade of the power car. The practical application showed that the FXD3-j EMUs meet the design requirements.